Agroecological evaluation of profiles with eroded arable and virgin soil in the pot experiment with pea at the northern part of steppe zone of Ukraine - Kharytonov, Mykola; Pashova, Valentina; Bagorka, Mariia; Mytsyk, Oleksandr; Tkalich, Yuriy; Lemishko , Svitlana (Ecological Questions, 2025)
The effective fertility of the humus horizon of mildly washed soil in terms of the productivity of aboveground mass of peas is the highest among all humus genetic horizons. The fertility of the upper horizon with very prominent humus accumulation (Hp), lower transition horizon, with little humus (Phc), and underlying parent material (Pc) horizons is 20% lower than the upper horizon with very prominent humus accumulation (H) horizon. The accumulation of macroelements by peas on the soils of virgin slopes is less than on the soils of arable slopes - by 18% for nitrogen, 36% for phosphorus, and 15% for potassium. The maximum accumulation of nitrogen, phosphorus and potassium by pea was on mildly sloped soil from the 0-10 and 10-20 cm layer comparative to moderately sloped one. The absorption of trace elements by pea depends on environmental conditions and can be divided into three groups: elements of high concentration - Fe, Mn, Zn, medium - Cu, Ni and Pb, and low - Co and Cd. An established pattern: the content of trace elements in plants grown in deeper layers decreases.